Biographical History of Manuel Balado: Contributions to the Development of Worldwide Neurosurgery: https://doi.org/10.59156/revista.v36i04.608 - Acuña, Marcelo; Cobos, Miriam (Revista Argentina de Neurocirugía, 2023)
Historical and biographical research of Manuel Juan María Balado, one of the first physician dedicated exclusively to neurosurgery, who laid the foundations of the specialty in Argentina and Latin America. His work, research and discoveries had an impact on the world scientific currents of the time, giving high profile to the Argentine school. Among his many contributions, works on the innervation of the iris, the optic pathway, the geniculate body and optochiasmatic arachnoiditis stand out, with his main contribution being the systematization of iodoventriculography that achieved global relevance until the appearance of computed tomography. This work covers the biography of a man who was overshadowed in medical history due to the importance of his discoveries.
Keywords: Biography; History; Manuel Balado; Neurosurgery